Citizen science and psychology: an evaluation of chances and risks - Funke, Joachim (Heidelberger Jahrbücher online, 2017)
Under the umbrella term of “Citizen Science”, a new paradigm for doing science is gaining attention. This article reviews the chances and risks associated with the new movement. Citizen Science is related to the broader “Open Science” movement and thus supports a paradigm shift in doing science. Psychological science will profit from opening itself up to interested non-professionals but at the same time, it has to watch out for and protect its scientific principles.